Immigration Supervision: The Existence of RW Police Policies as a Problem Solver for Immigration Violations in the Archipelago Work Area - Harahap, Amsal Rinaldy Syafii; Syahri, Muhammad Alvi; Aji, Koesmoyo Ponco (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The increase in the number of immigration violations in Indonesia in the 2022–2024 period indicates ineffectiveness in the supervisory function carried out by the Immigration Office's Technical Implementation Unit (UPT), especially due to limited numbers and territorial coverage.Purposes of the Research: This study aims to examine the potential of the Community Police (RW Police) policy as an alternative solution to support more effective immigration supervision down to the most remote areas.Methods of the Research: This research approach focuses on descriptive qualitative methods with literature studies and policy analysis of the Immigration Law, government policies, and academic literature. The aim is to understand the immigration supervision mechanism and evaluate the existence of the RW Police in handling immigration violations at the Technical Implementation Unit (UPT) in the archipelago work area.Findings of the Research: The results of the study show that collaboration between Immigration and the Police through the active role of the RW Police can be a form of effective preventive supervision, especially in detecting the presence and activities of foreigners in remote areas. In addition, information technology support has been proven to be able to increase operational efficiency and strengthen data integration between institutions. The implementation of this policy is expected to be able to reduce the number of immigration violations and strengthen state sovereignty through community-based supervision.